Integrating Digital Administration And Religious Commitment For Islamic Educator Pedagogic Performance: Mengintegrasikan Administrasi Digital Dan Komitmen Religius Untuk Kinerja Pedagogik Pendidik Islam - Isna Khoirunnisa; Sadam Fajar Shodiq (Halaqa: Islamic Education Journal, 2026)
General Background Digital transformation necessitates the adoption of digital learning administration systems for proper pedagogic management. Specific Background Within Islamic education, utilizing these technological frameworks requires a strong foundation of religious commitment to maintain professional values. Knowledge Gap Current literature frequently opposes technological advancement with spiritual principles, resulting in limited comprehensive models that unite both dimensions within educational settings. Aims This Systematic Literature Review investigates the integration of digital learning administration systems and religious commitment in shaping the pedagogic performance of Islamic education teachers. Results Based on a thematic synthesis of recent publications, the findings demonstrate that digital devices serve not merely as efficiency tools, but as vital instruments for actualizing the moral responsibilities of educators. These technological and spiritual components successfully merge to form a complete performance framework. Novelty This study establishes religious commitment as an essential ethical anchor that actively prevents the mechanization and human erosion of the teaching profession amid rapid digitalization. Implications Educational policymakers must restructure professional development programs so they do not merely focus on software literacy, but also prioritize strengthening the religious work ethic and Islamic digital ethics among teachers. Highlights Systematic reviews confirm technology acts as an instrument actualizing moral responsibilities. Spiritual values function as ethical anchors preventing the mechanization of modern teaching. Professional development policies must prioritize software literacy alongside strong theological work ethics. Keywords Digital Learning System; Ethical Anchor; Systematic Literature Review; Moral Responsibility; Islamic Education